2021
DOI: 10.3389/frobt.2021.540193
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between the Facial Flow Lines of Androids and Humans

Abstract: The behavior of an android robot face is difficult to predict because of the complicated interactions between many and various attributes (size, weight, and shape) of system components. Therefore, the system behavior should be analyzed after these components are assembled to improve their performance. In this study, the three-dimensional displacement distributions for the facial surfaces of two android robots were measured for the analysis. The faces of three adult males were also analyzed for comparison. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The coder found it difficult to differentiate AUs 6 (cheek raiser) and 7 (lid tightener). This is in line with earlier findings that androids struggled to replicate z-vector movements, including wrinkles and tension, compared with human expressions (Ishihara et al, 2021), owing to the physical constraints of artificial skin materials. The results of our intensity evaluation revealed that some AUs' maximum intensities were not realized.…”
Section: Discussionsupporting
confidence: 92%
“…The coder found it difficult to differentiate AUs 6 (cheek raiser) and 7 (lid tightener). This is in line with earlier findings that androids struggled to replicate z-vector movements, including wrinkles and tension, compared with human expressions (Ishihara et al, 2021), owing to the physical constraints of artificial skin materials. The results of our intensity evaluation revealed that some AUs' maximum intensities were not realized.…”
Section: Discussionsupporting
confidence: 92%
“…These AUs appear to reflect facial tension rather than facial movement, suggesting that not only the movement vector, which can be detected by the landmark detection algorithm, but also the approach, which can capture undulations in facial movements, will be necessary. In fact, recent studies have suggested that human faces have distinctive undulations when expressing each facial component [ 52 ]. Therefore, further development of RGB analyses or other information to subtly differentiate these AUs is desired.…”
Section: Discussionmentioning
confidence: 99%
“…Then, we used AdvancedSkeleton to add controllers to these points, in order to enable facial expression simulation in the humanoid head model. The movement displacements of the different parts were determined based on the research conducted by Ishihara et al [ 35 ], who tracked the three-dimensional positions of 125 Japanese male faces. Furthermore, when simulating the six basic facial expressions, the simulation was carried out with the aim of achieving the maximum intensity of each facial expression.…”
Section: Mechanical Design and Facial Expression Realization Of The H...mentioning
confidence: 99%